EP886 Atypical endometriosis associated with ovarian malignancy. (1st November 2019) - Kim, N; Hong, SR; Lim, KT; Lee, KH; Kim, TJ; So, KA
Abstract : Introduction/Background: Atypical endometriosis was first described by Czernobilsky and Morris in 1979. Atypical endometriosis shows dysplastic feature with the cellular atypia that is different from typical endometriosis. It is closely associated with endometriosis-associated ovarian malignancy. This study is to evaluate the clinical outcome of atypical endometriosis and its association with malignant malignancy. Methodology: A retrospective study included patients who diagnosed with atypical endometriosis between January 2001 and December 2017 at Cheil General Hospital & Women's Healthcare Center. All patients were surgically treated and histopathology was confirmed to atypical endometriosis. The clinical characteristics, histopathologic results were reviewed. Results: Among 13, 074 patients underwent endomteriosis surgery for the study period, 101 patients (0.8%) were diagnosed with atypical endometriosis. Ninety-eight patients of atypical endometriosis were analyzed and mean age was 34.8 years (range 16–58 years). Ten patients (10.2%) had previously undergone the endomteriosis surgery more than once. Atypical endometriosis associated with malignant ovarian tumor was found in 12 cases (12.2%); 9 cases of carcinomas and 3 cases of borderline tumor. There were classified as follows; five clear cell carcinomas, two endometrioid adenocarcinomas, one mixed clear cell and endometrioid adenocarcinoma, one seromucinous carcinoma, two mucinous borderline tumors, and one seromucinous borderline tumor. Among atypical endometriosis, the size of ovarian mass was significant difference between atypical endometirosis and ovarian malignancy (p=0.025). However the mean age (p=0.452), serum CA-125 (p=0.222), or CA-19-9 (p=0.464) was not different between two groups. Conclusion: The overall frequency of malignant transformation of enodmetriosis is 0.3–0.8%. In this study atypical endometriosis associated with malignant ovarian tumor was 12.2%. Atypical endometriosis is considerable precancerous and strongly associated with endometriosis-associated ovarian cancer. Increased awareness of the characteristics of atypical endometriosis will improve early detection of patients with endometriosis who are at risk of endometriotic-associated carcinoma. Disclosure: Nothing to disclose.